2005
DOI: 10.1242/dev.01848
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the head organizer in hydra involves the canonical Wnt pathway

Abstract: characteristics of the head organizer, as measured by transplantation experiments, and by the expression of genes associated with the head organizer. Hence, the role of the canonical Wnt pathway for the initiation of axis formation was established early in metazoan evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
303
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(322 citation statements)
references
References 56 publications
15
303
2
2
Order By: Relevance
“…Hydra's head organizer is located at the apical tip of the hypostome and was described for the first time by Browne (1909). When this hypostomal tissue is transplanted to ectopic positions along the body column of a host polyp it organizes a secondary body axis by recruiting host tissue (Technau et al, 2000;Broun and Bode, 2002;Broun et al, 2005). The hypostome is homologous to the blastopore of the cnidarian embryo and can be compared to the vertebrate organizer based on a conserved set of genes expressed in both organizers.…”
Section: Wnt Signalling During Organizer Formation and Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydra's head organizer is located at the apical tip of the hypostome and was described for the first time by Browne (1909). When this hypostomal tissue is transplanted to ectopic positions along the body column of a host polyp it organizes a secondary body axis by recruiting host tissue (Technau et al, 2000;Broun and Bode, 2002;Broun et al, 2005). The hypostome is homologous to the blastopore of the cnidarian embryo and can be compared to the vertebrate organizer based on a conserved set of genes expressed in both organizers.…”
Section: Wnt Signalling During Organizer Formation and Regenerationmentioning
confidence: 99%
“…Hyb-cat protein is localized at the apical membrane and in nuclei of epithelial cells. However, cells in the hypostome have much higher levels of nuclear b-catenin than cells in the body column ( Figure 3a) (Cramer von Laue, 2003;Broun et al, 2005) indicating that Wnt signalling is active in the hypostome. Wnt/b-catenin signalling is also active during bud formation.…”
Section: Wnt Signalling In the Hydra Head Organizermentioning
confidence: 99%
See 1 more Smart Citation
“…Both showed that activation of STK (Cardenas et al 2000;Cardenas and Salgado 2003;Manuel et al 2006;Arvizu et al 2006), GSK3 (Broun et al 2005), PKC, Pi3K, ERK 1-2 (Manuel et al 2006;Arvizu et al 2006), MAPK and RSK (Kaloulis et al 2004;Chera et al 2011) are indeed necessary over the first hours following bisection (see…”
Section: Activation Of Stk Pi3k Erk and Mapk Pathways During Head Bmentioning
confidence: 99%
“…Cette induction de l'expression du gène Wnt3 correspond au moment où l'activité organisatrice commence à apparaître dans le bourgeon, comme l'ont montré les expériences de transplantation (MacWilliams, 1983;Broun et al, 2005;Lengfeld et al, 2009). Parmi les différents gènes de type Wnt, Wnt3 est effectivement le premier dont l'expression est induite, ce qui suggère que Wnt3 joue un rôle instructeur dans la formation du centre organisateur.…”
Section: Les Cellules Apoptotiques Source De Signalisation De La Voiunclassified